On the issue of the formation and development of science as a social institution - E. S. Nesterenko (Вестник университета)
The relevance of scientific research on the specifics of the institutional environment for the development of the Institute of Science in the Russian Federation is associated with the rapid development of the digital economy, in which the development of science is becoming the most important factor in ensuring Russia's competitiveness on the world stage. The author conducted a comprehensive study of the specifics of the institutional environment of the development of the Institute of Science in the Russian Federation. The article studies the stages of formation and development of science as a certain social institution. The paper presents the criteria of institutionalization and it is established that the Institute of Science meets them. The study highlights the purpose and functions of science as a social institution. The paper also proposes the institutional environment for the functioning of the Institute of Science, taking into account the state and the individual as an integral part of successful development. The author concludes that science as a social institution is a self-organizing, self-regulating and self-developing system based on the realization of human potential through special tools of scientific activity and special organizations and aimed at the production and dissemination of scientific knowledge.